Upaya Pelestarian Budaya di Era Globalisasi Melalui Pendidikan Kewarganegaraan - Aini Shifana Savitri; Dinie Anggraeni Dewi; Rizky Saeful Hayat (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2024)
Indonesian culture has local culture originating from each region. Indonesia is a country that is rich in culture and diverse. Indonesian culture has changed from time to time because of the people themselves who want change. These changes are increasingly visible rapidly with the inclusion of elements of globalization into Indonesian culture. Education is the most important area in shaping the character of the younger generation to prevent the flow of globalization which can damage morals. Through education, the character of the younger generation can be saved by learning Citizenship Education. This research uses qualitative research methods or a descriptive approach. The results of this research show that in citizenship education, students are given an understanding of the values ​​of Pancasila and an introduction to Indonesian culture. This can shape character in facing the era of globalization which is increasingly having a negative impact on the character of the younger generation